2016
DOI: 10.1007/s00347-015-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatische Aspekte beim trockenen Auge

Abstract: Patients with therapy-resistant dry eye syndrome often suffer from anxiety and depression. The psychological stress acts on the nervous system to suppress lacrimal gland function. Further investigation of the correlation between the lacrimal tear film phase and psychological disorders is recommended. Knowledge of personality disorders may allow psychological support that would improve the treatment options for dry eye syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
8
0
5
Order By: Relevance
“…Taking into account the growing number of publications on the combination of DES with psychiatric conditions, as well as the presence of obsessive-compulsive disorder in the described patient, it could be assumed that the latter induced her DES [20][21][22]. In particular, the mechanisms of DES development could also be influenced by stress-induced suppression of lacrimal gland function [23].…”
Section: Discussionmentioning
confidence: 93%
“…Taking into account the growing number of publications on the combination of DES with psychiatric conditions, as well as the presence of obsessive-compulsive disorder in the described patient, it could be assumed that the latter induced her DES [20][21][22]. In particular, the mechanisms of DES development could also be influenced by stress-induced suppression of lacrimal gland function [23].…”
Section: Discussionmentioning
confidence: 93%
“…These findings suggest that health anxiety, depression and anxiety may affect the development of dry eye symptoms and may be one of the causes of the inconsistency between symptoms and signs of DED 28,29. Nepp30 showed that patients with DED recalcitrant to treatment often have anxiety and depression and also postulated that the psychological status influenced the nervous system to suppress tear secretion from the lacrimal gland 30…”
Section: Association With Psychiatric Problemsmentioning
confidence: 99%
“…Bu çalışmada kuru göz hastalarında depresyon puanı istatistiksel olarak anlamlı olmasa da kontrol grubuna göre daha yüksek bulundu. Bireylerde KGS semptomlarının anksiyete ve depresyona eğilimi artırmasının yanında, psikolojik stresin de çeşitli yollarla KGS'na yol açtığı bilinmektedir (24)(25)(26). Tedaviye dirençli KGS'da psikolojik bozuklukların analizinin yapıldığı bir araştırma da hastaların %52,7'sinde psikolojik bozukluk saptanmıştır.…”
Section: Bulgularunclassified
“…%22,7'sinde ise psikolojik bozukluk saptanmamıştır. Çalışmada, psikolojik stresin sinir sistemine etki etmesi yoluyla lakrimal bez fonksiyonunu baskılanmasının bu sonuçları ortaya çıkardığı belirtilmiştir (24). Hem KGS hem de depresyon pek çok ortak etyolojik faktöre sahiptir.…”
Section: Bulgularunclassified